VD_FINDINFO Décision / 2013 / 924 vom 14. August 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL, PRÉVENU, ACQUITTEMENT | 319 CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH)